Antibiotic residues in meat, milk and aquatic products in Shanghai and human exposure assessment. (October 2017) - Wang, Hexing; Ren, Lingshuang; Yu, Xin; Hu, Jing; Chen, Yue; He, Gengsheng; Jiang, Qingwu
Abstract: In this study, we screened 20 common antibiotic (three tetracyclines, four fluoroquinolones, three macrolides, three β-lactams, four sulfonamides, and three phenicols) residues in 125 samples from common types of livestock and poultry meat, milk and aquatic products in Shanghai by ultra-performance liquid chromatography coupled to high-resolution quadrupole time-of-flight mass spectrometry in 2016 and assessed their role in human exposure by Monte Carlo Simulation. Overall, 15 out of screened antibiotics were found in these samples and the overall detection frequency was 39.2%. Antibiotics were found in 28.6% of livestock and poultry meat (35.3% for pork and 22.2% for chicken), 10.6% of milk, and 52.1% of aquatic products. Of aquatic products, the overall detection frequency of antibiotics was 91.7% for snakeheads, 81.8% for loaches, 76.9% for carps, 40.0% for yellow-head catfishes, and 16.7% for shrimps, but none was detected in swamp eels. Four human antibiotics were detected: azithromycin was detected in 50.0% of snakeheads and 5.1% of loaches, roxithromycin in 5.9% of pork, and chloramphenicol and cefradine respectively in 5.3% of milk. Enrofloxacin and trimethoprim exceeded the maximum residue limits in 7.7% of carps and 8.3% of snakeheads, respectively. The estimated daily exposure dose by Monte Carlo Simulation was less than 1 μg/kg/day. Antibiotic residues in aquatic products and their consumption accounted for 74.71% and 70.35% of overall variance of estimated antibiotic exposure for men and women, respectively. These findings indicated a high level of antibiotic residues in meat, milk and aquatic products and aquatic products were an important source for exposure of human to antibiotics. Highlights: Fifteen of 20 antibiotics were found with an overall detection frequency of 39.2%. Antibiotics occurred in 28.6% of meat, 10.6% of milk, and 52.1% of aquatic products. The estimated daily exposure dose by Monte Carlo Simulation was below 1 μg/kg/day. Aquatic products were an important source for exposure of human to antibiotics. Enrofloxacin and trimethoprim exceeded their MRLs in some fish samples.